Analisis Hubungan Faktor Psikososial terhadap Stres Kerja dan Perilaku Berisiko Karyawan di PT. X - Putro, Aji; Erwandi, Dadan; Kadir, Abdul (UI Scholars Hub, 2021)
The death rate due to elevators in the world at 1999-2009 was 263 people, caused by 57% falling, 18% being pinched, 17% falling by objects, and 9% other causes. One of the efforts to prevent accidents was to analyze psychosocial factors that caused work stress and at-risk behavior that can lead to work accidents. This study aimed to determine the relationship of psychosocial factors to work stress and the at-risk behavior of employees at PT. X is engaged in the elevator and escalator sector. This research method was a descriptive quantitative, cross-sectional study with 200 people. Psychosocial factors related to workload and work speed, job control, organizational function, interpersonal relationships, organizational roles, career development, home-work interface, psychological demands, participation or supervision, bullying and violence. There is a relationship between work stress and at-risk behavior. Behaviors that often arise when employees experience work stress are rushing at work decisions. The highest work stress complaints were related to physiological complaints, namely the consumption of headache relievers; behavioral complaints, namely interrupting and cutting other people's sentences; emotional complaints, namely refusal to go to work; Cognitive complaints are difficulty thinking clearly and concentrating. PT X should conduct a more comprehensive risk assessment, clarify career development, and recalculate the workload, effectiveness and efficiency to prevent negative impact on employees' work-life balance.